Gene-gene interaction of AhRwith and within the Wntcascade affects susceptibility to lung cancer - Rosenberger, Albert; Muttray, Nils; Hung, Rayjean J.; Christiani, David C.; Caporaso, Neil E.; Liu, Geoffrey; Bojesen, Stig E.; Le Marchand, Loic; Albanes, Demetrios; Aldrich, Melinda C.; Tardon, Adonina; Fernández-Tardón, Guillermo; et al. (European journal of medical research, 2022)
Aberrant Wnt signalling, regulating cell development and stemness, influences the development of many cancer types. The Aryl hydrocarbon receptor (AhR) mediates tumorigenesis of environmental pollutants. Complex interaction patterns of genes assigned to AhR/Wnt-signalling were recently associated with lung cancer susceptibility.
Gesehen am 16.03.2022